Restricted left atrial dilatation can visually differentiate cardiac amyloidosis from hypertrophic cardiomyopathy. (27th May 2021) - Higashi, Haruhiko; Inoue, Katsuji; Inaba, Shinji; Nakao, Yasuhisa; Kinoshita, Masaki; Miyazaki, Shigehiro; Miyoshi, Toru; Akazawa, Yusuke; Kawakami, Hiroshi; Uetani, Teruyoshi; Aono, Jun; Nagai, Takayuki; et al.
Abstract: Aims: Cardiac amyloidosis (CA) is an infiltrative myocardial disease that occasionally mimics hypertrophic cardiomyopathy (HCM). The aim of this study is to investigate the discriminatory ability of visual assessment of left atrial (LA) function between CA and HCM on echocardiography. Methods and results: In total, 93 patients with cardiac magnetic resonance imaging (CMR)‐confirmed HCM and 34 with cardiac biopsy‐confirmed CA were retrospectively assessed. LA dilatation was assessed via echocardiography in an apical four‐chamber view. Visual assessment was performed to identify LA dilatation grade (preserved = 1, abnormal = 2, and restricted = 3) based on the extent of outward expansion in the LA reservoir phase. Regarding the reproducibility of visually assessing LA dilatation grade, the kappa values between intra‐ and inter‐observer measurements were 0.82 and 0.70, respectively. Of 127 participants, 57 (45%), 42 (33%), and 28 (22%) presented with LA dilatation Grades 1, 2, and 3, respectively. All 57 patients with preserved LA dilatation (Grade 1) had HCM, and 20 of 28 patients (71%) with restricted LA dilatation (Grade 3) presented with CA. Patients with CA had a higher LA dilatation grade than those with HCM ( P  < 0.01). LA emptying fraction and reservoir strain were also quantitatively evaluated. The area under the curves of LA dilatation grade (0.88) and LA emptying fraction (0.88) for differentiation of these two diseases were higher than that of LA reservoir strain (0.73) ( P  < 0.01, respectively). During follow‐up, nine patients with HCM and 16 with CA experienced cardiac event (cardiac death or hospitalization due to heart failure). In Kaplan–Meier analysis including both groups of HCM and CA, the incidence of cardiac events was higher in patients with restricted LA dilatation than in those with preserved or abnormal LA dilatation (log‐rank test, P  < 0.01). Conclusions: Restricted LA dilatation is an indicator for the diagnosis of CA. Further, visual assessment of abnormal LA motion may facilitate diagnosis in patients with CA and high‐risk patients with HCM.